B11 Pong, the posterior (pericapsular) nerve group radiofrequency as possible adjunct to treat chronic hip pain. (11th August 2022) - Del Buono, R; Terranova, G; Pascarella, G; Costa, F; Genco, D; Roli, S; Grossi, PA
Abstract : Background and Aims: Chronic hip pain is a cause of disability and costs. There are some available options to threat this condition, such as radiofrequency ablation or chemical denervation. An innovative approach to treat posterior hip pain due to inoperable femur fracture has recently been described [1]. We share a strategy to manage severe chronic hip pain in an old patient unwilling to undergo hip surgery. Methods: Firstly, a test with a PENG block combined a posterior approach (PONG) has been performed. The PONG was administered with the same technique described for hip surgery [2, 3]. After the positive test response, the patient underwent anterior and posterior hip radiofrequency (RF) ablation/neuromodulation. Anterior RF ablation has been performed under ultrasound and fluoroscopic guidance as per current recommendations. Posteriorly, a variant of the Kwung-Tung approach was used under RF stimulus guide, locating two different spots. Under ultrasound, the inferior spot corresponded to the capsule deep to the quadratus femoris, while the superior spot corresponded to the superior-posterior border of the acetabulum. Pulsed RF until 42°C for 5 minutes was performed posteriorly on each spot. NRS was registered before the procedure, and after a one-month follow-up. Results: Previous patient's NRS score was 7 for static pain in sitting position, and 9 for dynamic pain. After one month, static NRS decreased to 2, while dynamic pain was 6. No adverse effects were reported. Conclusions: The combination of anterior and posterior RF intervention on chronic hip pain provided a viable alternative in a patient unwilling to undergo hip surgery.